Regulation of hepatic blood flow by feeding conditions in sheep: a meta-analysis - Vernet J.; Nozière P.; Sauvant D.; Léger S.; Ortigues-Marty I. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
The relationships between hepatic blood flows and dietary intakes by sheep were evaluated by meta-analysis of published data. The influence of dry matter intake (DMI) and of metabolisable energy intake (MEI) were quantified after selection of the publications that presented sufficient variations in the independent variables. In fed sheep, increments of 1 g DMI /(d.kg BW) increased blood flows by 61, 20 and 81 ml/(h.kg BW) in portal vein, hepatic artery and hepatic vein, respectively and increments of 1 kJ MEI/(d.kg BW) increased flow by 5.7, 2.0 and 7.8 ml/(h.kg BW), in the respective vessels (P<0.01). In fasted vs fed sheep, the response was lower. The contribution of hepatic arterial to total hepatic blood flow was independent of both fasting and feeding level.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)